Kendala-kendala Anak Usia Dini dalam Mengamalkan Al-Qur’an di Era Digital - Rohmah, Siti; Sutrisno, Sutrisno (FITK UIN Walisongo Semarang, 2024)
All Muslims believe that the Koran is the main source of Islamic teachings. The above are mandatory religious teachings, and a person cannot be called a good Muslim if he violates these beliefs. Thus, every Islamic educational institution must truly make the Koran the main material that must be studied. Read or recite the Koran, write, memorize, and be able to practice the religious values contained in the Al-Qur'an. Using the Koran as a guide to life is a competency that Muslim children must have. So what are the obstacles for young children in practicing the Koran? The above is a big problem in this research, the answer to which must be sought through a qualitative approach. The research subjects were 3 teachers and students at Nw Sajang Kindergarten. In order to obtain accurate data, researchers used interview and observation techniques. Based on the results of research and discussions that have been carried out, there are two obstacle factors, namely internal and external factors experienced by Nw Sajang Kindergarten children in learning to practice the Al-Qur'an. Also internal factors are: (1). Lack of concentration. (2). Difficulty reading Arabic letters. (3). Limited understanding of Arabic. (4). Pressure or lack of time for studying religion, especially the Koran. (5). Lack of motivation and strong will from the child. And the external factors are: (1). Environmental disturbances (2). Children play more often. (3). Lack of appropriate learning materials. (4). Children use electronic devices more often when they are at home. And the solution to overcome this obstacle is; increasing concentration, taking an educational game approach, integrated Arabic language teaching, effective time management, providing ongoing motivation, and finally creating a calm learning environment.